2003
DOI: 10.1046/j.1440-1797.2003.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus infection and related risk factors among Iranian haemodialysis patients

Abstract: Hepatitis C virus (HCV) infection is common among patients undergoing haemodialysis, and liver disease is an important cause of morbidity and mortality in this population. Management of HCV-related liver disease is a major health concern in patients with end-stage renal disease (ESRD) undergoing haemodialysis. To investigate the prevalence of HCV infection in patients on haemodialysis and its associated risk factors, we conducted a prospective case series study of 838 patients on haemodialysis in Tehran, Iran.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 27 publications
2
46
3
Order By: Relevance
“…Two HCV genotypes were identified in these patients in Ahvaz city: subtypes 1a and 1b. Subtype 1a was predominant (60%) similar to the recent studies in different populations in the region (18,21). This finding is different from HCV genotypes distribution and the high frequency of genotype HCV 1a/1b plus HCV 4 and HCV 2/2a plus HCV 4in multi-transfused patients living in neighbouring countries, such as Bahrain and Saudi Arabia respectively, sharing sea boarder with Khuzestan province (4).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Two HCV genotypes were identified in these patients in Ahvaz city: subtypes 1a and 1b. Subtype 1a was predominant (60%) similar to the recent studies in different populations in the region (18,21). This finding is different from HCV genotypes distribution and the high frequency of genotype HCV 1a/1b plus HCV 4 and HCV 2/2a plus HCV 4in multi-transfused patients living in neighbouring countries, such as Bahrain and Saudi Arabia respectively, sharing sea boarder with Khuzestan province (4).…”
Section: Discussionsupporting
confidence: 73%
“…Recent studies of SCA patients show that the prevalence of anti-HCV varied (4.5 to 21%) (2,(11)(12)(13), which suggests that the geographical area may affect the potential risk of HCV in patients (17)(18)(19). Moreover, one of the most common causes of HCV transmission by transfusion is the occurrence of new infections in blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in several studies, HCV infection is a significant health problem in dialysis units in our country with a high prevalence rate (13.2%) among this population [20] . It was reported that blood transfusion and duration of dialysis treatment are important risk factors for HCV infection in patients on haemodialysis [21,22] .…”
Section: Discussionsupporting
confidence: 52%
“…Recently the thalassaemia data bank has been reported that the prevalence of HCV infection in these patients is 16%. It has also reported that over 70% of thalassaemia patients in Iran are older than 10 years [29]. In Iran, the prevalence of anti-HCV in hemophiliac is from 15.65% to 76.7% in patients from various geographical regions [30].…”
Section: Discussionmentioning
confidence: 99%